2022
DOI: 10.3389/fpsyg.2022.1048635
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of language and visual art integrated teaching on language learning performance and satisfaction of ethnic minority students in China

Abstract: Innovative technological products are present in students' environments. Information explosion and popularity are affecting their thoughts, and there is a large amount of information fuel in life through the Internet, television, movies, and advertisements. This phenomenon transforms reading from pure words into image. The current study was conducted using an experimental design model. A total of 188 ethnic minority students in the Hebei Province participated in the experimental study. The experimental group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Afterward, the present study embraces the Social Inequality Gap Reduction [ 10 ], which is buoyed by an abundance of literature that stresses that economically disadvantaged children benefit from ECAs more than privileged children [ 32 , 34 , 38 ]. In addition, this paper considered OOS activities supervised and organized by parents to enhance children’s ECA cognition, emotion, and self-efficacy [ 12 , 15 , 27 ]. Strangely, this paper found that children’s SES does not determine the chance of being in structured OOS visual art activities organized by private training schools, which aligns with the latest study assumption [ 32 ] and contradicts with Chinese literature that found the positive association between parental SES and the likelihood of their children participating in different ECAs [ 1 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, the present study embraces the Social Inequality Gap Reduction [ 10 ], which is buoyed by an abundance of literature that stresses that economically disadvantaged children benefit from ECAs more than privileged children [ 32 , 34 , 38 ]. In addition, this paper considered OOS activities supervised and organized by parents to enhance children’s ECA cognition, emotion, and self-efficacy [ 12 , 15 , 27 ]. Strangely, this paper found that children’s SES does not determine the chance of being in structured OOS visual art activities organized by private training schools, which aligns with the latest study assumption [ 32 ] and contradicts with Chinese literature that found the positive association between parental SES and the likelihood of their children participating in different ECAs [ 1 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, children who participate in OOS ECAs outdo their counterparts in social adjustment, psychological well-being, and academic performance [ 5 , 14 ], whereas low-income children spend their after-school time with activities that have no substantial benefit for them, perhaps destroying their future [ 9 , 15 ] such as watching TV, playing games [ 8 ]. Although many studies have highlighted the robust impact of OOS ECA participation on children’s development, it is still controversial to generalize its generic effect due to the paucity of concrete evidence [e.g., 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%